Psychometric properties of the Icelandic version of the Worry and Anxiety Questionnaire in a clinical and a general sample - Hulda Sveindís Jóhannesdóttir 1990- (2019)
Limited research has been conducted on the psychometric properties of self-report measures for Generalized Anxiety Disorder (GAD) in Icelandic samples. By translating the Worry and Anxiety Questionnaire (WAQ) into Icelandic and assess its psychometric properties, in a general and a clinical sample, the aim of the current study was to amend this. The general sample consisted of 110 males (42.97%) and 146 females (57.03%), a total of 256 participants (Mage = 25 years, age range: 18 -47 years, SD = 5.6), from the University of Reykjavík who answered seven self-report measures. For the general sample, the WAQ demonstrated excellent internal reliability (α = .92), satisfactory convergent validity with other measures of GAD (r = .54 - .78) and, an adequate discriminant validity (r = .46-.72). A principal axis factor analysis revealed a one factor solution. For the clinical sample, participants (N = 21, Mage = 30.1 years, age range: 41 years, SD = 9.18) were recruited from three psychiatric outpatient units, where they answered 10 self-report measures. The mean age was 28.80 (SD = 4.08). The WAQ displayed sufficient internal reliability (α = .72) in the clinical sample. The difference between the general and clinical sample on the WAQ total score was significant. It is concluded that the Icelandic version of the WAQ is a reliable and valid self-report measure in a general sample, but further studies are needed in for clinical samples. Takmarkaðar rannsóknir hafa verið gerðar á mælitækjum sem meta almenna kvíðaröskun (GAD) á Íslandi. Þessi rannsókn sækist eftir að bæta úr því með því að þýða sjálfsmatskvarðann „the Worry and Anxiety Questionnaire“ yfir á íslensku og meta próffræðileg eiginleika í almennu og klínísku úrtaki. Allir þátttakendur í almenna úrtakinu svöruðu sjö sjálfsmatskvörðum en í heild tóku 256 einstaklingar þátt (Maldur = 25 ár, spönn: 18-47 ár, sf = 5.6). Úrtakið skiptist í 110 karla (42.97%) og 146 konur (57.03%), allt nemendur við háskólann í Reykjavík. Mælingar í almennu úrtaki sýndu fram á ágætan ...